Analysis of Judges' Legal Considerations Against the Sale of Joint Assets Without the Wife's Agreement in the Study of Positive Law in Indonesia - Галанг Лазуарді; Сулістандарі .; Сіті Кунарті (Проблеми Законності, 2023)
The sale and purchase of land rights is usually carried out by means of an agreement or what is known as a land rights sale and purchase agreement. In the case of the transfer of land rights, the formal conditions for the sale and purchase of land rights must be proven by a deed of sale and purchase drawn up by and before an authorized official. Before the sale and purchase agreement is carried out, it is usually done with the initial agreement which the deed is drawn up by a notary. The responsibilities of a notary as a public official include the responsibilities of the notary profession itself which are related to the deed, including, the responsibility of a notary in civil terms for the deed he makes relates to the material truth of the deed. Then regarding joint assets that are sold without the consent of the husband and/or wife, is it possible, and does the notary have any responsibility for that. Then there is a court decision regarding joint assets which legalizes the sale and purchase deed because of the good faith buyer's consideration as stipulated in the Supreme Court Circular Letter No.  7 of 2012. The purpose of this study is to analyze the responsibility of a Notary related to the sale and purchase of joint assets and the legal considerations of judges who decide cases based on a circular letter which is not a general rule but an internal one that is not well known to the public. The research method used is normative, using secondary data obtained from library research including primary, secondary and tertiary legal sources. The responsibility of the notary, namely in making the deed of sale and purchase of joint property, is a civil responsibility, that is, all the regulations regulated in the UUJN only provide sanctions for violations of a formal notary, for example the rules for issuing deed and others. Judges should in deciding a case use general rules that are understood and understood by the community instead of using internal rules from the court itself which are not understood by the community, especially regarding buyers with good intentions.